Content analysis of advertisments in different cultures - Lazović, Vesna (ELOPE (Ljubljana), 2012)
Increasingly, advertising examples are being analyzed and used as yet another form of communication, on account of their ubiquity (e.g. billboards, Internet, television, magazines). Designed to compel us to purchase products, advertisements have the potential to greatly impact our lives. They show current trends in social preferences, they reveal cultural values and norms of the target audience and, finally, they can be the mirror of the times people live in. The purpose of this paper is to give a brief overview of the findings in previously carried-out research relating to cross-cultural content analysis of advertisements. The reports have addressed both linguistic and extra-linguistic features and trends in advertising and emphasized language- and culture-specific elements. This paper also gives ideas for future studies, since nowadays, due to international marketing and increasing globalization there are more cultural transfers to be explored, as cultures are coming in contact far more frequently.
Keywords: advertising; analiza vsebine; medkulturna analiza; oglaševanje